RELIABILITY ANALYSIS OF A STEEL BEAM USING THE MONTE CARLO METHOD (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
This paper aims to show the feasibility of structural analysis in steel beams, based on the precepts of reliability. We assessed the reliability and security of a steel I-beam profile (I 254 (10”) x 37,7), MR250, subject to an applied bending moment. The purpose was to evaluate the appropriateness of the component in handling specific project stresses. First we provide a dimensioning analysis based on Brazilian structural standards and then a verification of the beam’s relative safety, in terms of the reliability index ï¢ . The adopted failure function is related to gross and net areas of the flange, submitted to traction stresses. The system’s reliability index, constituted by the failure function is also determined. Considering the statistical results, the failure rate in the structure, demonstrates that the solicited project loadings are sustained, also determining the capacity of the structure to exceed the applied load, while maintaining structural safety of the steel beam. In the reliability analysis, the use of randomized integer generation, assisted by computational resources (Mathcad), makes it feasible to infinitely test the metallic structure. The Monte Carlo method was used, based on determined probability distributions (involved variables), to obtain the probability of structural failure. The random variables used in the reliability analysis, are delineated by the Joint Committee for Structural Safety (JCSS).